1980
DOI: 10.1002/j.1551-8833.1980.tb04541.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Technology to Meet the Interim Primary Drinking Water Regulations for Inorganics: Part 5

Abstract: The fifth in a series summarizing existing treatment technology to meet the inorganic National Interim Primary Drinking Water Regulations, this report describes current methods for removing barium and radionuclides from drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A number of studies have shown that radium adsorbs and/or coprecipitates to many substances that commonly exist in water treatment plants and distribution systems (5)(6)(7)(8)(9)(10)(11)(12)(13). Valentine (10,12) found that linear sorption isotherms described the adsorption of radium to hydrous iron and manganese oxides.…”
mentioning
confidence: 99%
“…A number of studies have shown that radium adsorbs and/or coprecipitates to many substances that commonly exist in water treatment plants and distribution systems (5)(6)(7)(8)(9)(10)(11)(12)(13). Valentine (10,12) found that linear sorption isotherms described the adsorption of radium to hydrous iron and manganese oxides.…”
mentioning
confidence: 99%
“…7.9 Removal efficiency of Ba*+ at two fullscale ion exchange softening plants has been reported. 7 The first plant showed a reduction from 10 mg Ba2+/L to less than 1 mg/L for 153 bed volumes (BV) of water processed, and the second showed a reduction from 19 mg Ba2+/L to 1 mg/L or less for 100 bed volumes. The influent water at both plants contained 220-230 mg hardness as CaCOa/L.…”
mentioning
confidence: 99%